Contact plan design based on bi-directional particle swarm optimization in satellite network - Cuiqin DAI; Huang TANG; Linfeng GUO (Tongxin xuebao)
Aiming at the problems of time-varying topology,intermittent connection,and constrained resource in satellite network,a contact plan design (CPD) scheme based on bi-directional particle optimization (BPSO) algorithm was proposed.Firstly,the task-based time-expanded graph (TEG) model was constructed through the analysis of resource-constrained time-varying satellite network.Next,available contact plan (CP) in satellite network were generated through initialization,coding and repairing by considering the discreteness of network topology and the limitation of node resources.Then,an evaluation function was designed according to the characteristics of the execution task to distinguish whether the generated available CP was good or bad.Finally,the bits to be corrected in the worst location were determined according to the sparse characteristics of links in CP,and the CP was continuously modified by the proposed BPSO algorithm to optimize the performance of spatial data transmission.The simulation results show that the proposed BPSO-based CPD scheme can effectively reduce the task delivery time and increase the task arrival rate.